AE source localization and imaging on cylindrical shell structures based on six-AE-sensor monitoring network and VTR focusing imaging. Issue 1 (2nd January 2021) - Wang, Shaofeng; Wang, Hailing; Wang, Daorui; Wang, Jianguo; Zhang, Wenliang; Hong, Jun; Gao, Lin
ABSTRACT: This study is interested in how to utilise the virtual time reversal (VTR) technique to locate the continuous AE source in cylindrical shell structure. Thus, a six-AE-sensor monitoring network was designed to divide cylindrical surface into two symmetric semi-cylindrical monitoring areas whose four vertexes and two geometrical centres were defined as the measuring points. The AE source can be located in certain semi-cylindrical monitoring area whose centre measuring point first captured the emitted AE signal. Besides, the response signals at other four measuring points were used to localise the AE source. To realise the VTR focusing of the AE signals, the proposed method solved two key problems. One is to search the shortest helical path between two arbitrary points on a cylindrical surface, which can provide the shortest distance from AE source to sensor. The other is to extract the specific frequency coefficients of wavelet transform for the continuous AE signal, which can meet with the requirement for the instantaneous abrupt characteristic of the signals to be processed using VTR focusing technique. Finally, a continuous leak experiment was carried out on a gas-filled steel pipe. The corresponding localisation method can accurately estimate the location of the continuous leak source.